ส่วนประสมการตลาดที่มีผลต่อผู้บริโภคในอำเภอเมืองสมุทรสาครในการเลือกบัตรเครดิตที่ออกโดยธนาคารพาณิชย์ - กุลธิดา สาครสง่าศักดิ์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This independent study aimed to examine the marketing mix factors affecting customers in Mueang Samut Sakhon District towards selecting credit cards issued by Commercial Banks. In this study, questionnaires were used to collect data from 400 customers of credit cards issued by Commercial Banks in Meuang Samut Sakhon. The convenience sampling technique was used and were analyzed by descriptive statistics such as frequency, percentage and means. The findings presented that the majority of the respondents were female, age between 30 – 39 years old, the level of education was bachelor, characterized as unmarried, there are 15,000-29,999 baht average monthly income and worked as private company employees. The majority of respondents most frequently used credit card issued by Kasikornbank Public Company Limited, there are reasons to use credit card were privileges of credit card, there are using the credit card for benefits were facility in paying goods and services, there are using the credit card for paying goods and services type food and beverage and there are counselor using the credit card were decision myself. The study’s results of marketing mix factors affecting customers in Meuang Samut Sakhon District towards selecting credit cards issued by Commercial Banks found that the respondents considered marketing mix factor at high level of importance on place, promotion, product and price factors, respectively. The highest level of each sub marketing factor was shown hereafter. In Product, the highest score was there chip card prevent counterfeiting and copying card information. In Price, the highest score was the fee for the service through various channels. In Place, the highest score was can contact bank 24 hours a day and In Promotion, the highest score was special discount from using the credit card for buying goods and services.